SANTOS, Irene; SILVA, Cidinha da; FIALHO, Dorvalina E. P.; BARCELLOS, Vera Daisy; BETTIOL, Zoravia. Colonos e Quilombolas. Memória fotográfica das colônias africanas de Porto Alegre. Porto Alegre: [s/n], 2010. - Rechenberg, Fernanda (ILUMINURAS, 2013)
SANTOS, Irene; SILVA, Cidinha da; FIALHO, Dorvalina E. P.; BARCELLOS, Vera Daisy; BETTIOL, Zoravia. Colonos e Quilombolas. Memória fotográfica das colônias africanas de Porto Alegre. Porto Alegre: [s/n], 2010.